A disciplina de língua portuguesa no contexto do currículo oficial da Secretaria de Estado da Educação de São Paulo - Catarino, Roberta Camargo (2014)
Interest in this research originates from a set of measures proposed by the government of of São Paulo in 2007, during of the government of José Serra . Called São Paulo faz Escola, this set of actions and measures set goals to be achieved by 2010 . The actions include curriculum reform and its transformation into the Official Curriculum in 2010 . Our object of study is part of the curriculum reform that was proposed for middle school students , specifically the Portuguese language curriculum offered by the Department of Education of São Paulo . The study focuses its attention initially on how, along the past decades, literature teaching was presented through different curricular proposals . This study includes the proposal of the Coordination of Studies and Pedagogical Standards, developed in the 1980s, the National Curricular Parameters , in the 1990s , and the Official Curriculum of São Paulo , in 2010. At a second stage, this research seeks to understand how teachers of Portuguese language have appropriated these different proposals in the context of their work . The survey was conducted through official document analysis and interviews . The official documents and interviews of teachers are the primary sources of this research . The survey results indicate that the main contribution of the Official Curriculum for the work done by teachers is related to an equal education for all, which can be regarded as a guiding teaching work. As for the teaching of literature, presented by Official Curriculum, this should be spiral shape, the matters discussed themes run, working the social context in wich the works were created, in no way chronological. However, despite this change, the survey data allow us to state that the teaching of literature in the classroom, still being carried out the way it was done before the Official Curriculum.